MicroRNA-Based Diagnosis and Therapeutics for Vascular Cognitive Impairment and Dementia - Zhai, Weijie; Zhao, Meng; Zhang, Guimei; Wang, Zicheng; Wei, Chunxiao; Sun, Li (Frontiers in Neurology, 2022)
Vascular cognitive impairment and dementia (VCID) is a neurodegenerative disease that is recognized as the second leading cause of dementia after Alzheimer's disease. The underlying pathological mechanism of VCID can include a dysregulated immune response, oxidative stress, hypotension, hypoperfusion, and perivascular clearance dysfunction. Despite the high incidence of VCID, no effective therapies are currently available for preventing or delaying its progression. Recently, the pathophysiological role of microRNAs (miRNAs) in VCID has shown promise as novel diagnostic biomarkers and therapeutic targets. Studies have revealed that miRNAs can regulate the function of the blood-brain barrier, affect apoptosis and oxidative stress in the central nervous system, and modulate neuroinflammation and neurodifferentiation. Thus, this review summarizes recent findings on VCID and miRNAs, focusing on their correlation and contribution to the development of VCID pathology.